Estimation of cellular immune response by evaluation of some cytokines in immunopathogenesis of chronic hepatitis B and C pre- and post- treated Iraqi patients (in vivo and in vitro) (Baghdad Science Journal, 2009)
Two groups of chronic hepatitis B and C virus patients were divided into Pre-treated patients (25 CHB patients with positive HBs Ag for more than 6 months and 40 CHC patients), and post-treated patients [12 CHB patients (4, 6, and 2 were treated with lamivudine, IFN-? and combination of LMV + IFN-? respectively), and 27 patients for CHC (3, 13 and 11 patients were treated with Ribavirin, IFN-? and combination therapy (RBV+ IFN-?) respectively].These patients were followed up for 6 months.By using ELISA technique, levels of IL-6, IL-10, IFN-? and TNF-? were measured in vivo and in vitro (supernatant of PBMCs stimulated with PHA) and compared with healthy control. The mean level of IL-6, IL-10 and TNF-? in CHB patients showed significant differences (P